Automated justice? A study on the interdisciplinarity between artificial intelligence and law in the administration of justice and recommendations for its development and regulation - Bedregal Aguilar, Alex David (2025)
The purpose of this research is to systematize the progress made in the interdisciplinary interaction between law in the administration of justice and artificial intelligence, in order to establish guidelines for its study, legal development, and regulation. First, the concept of artificial intelligence will be defined, along with its scope and the concerns raised by its incorporation into the legal field. Subsequently, the advances resulting from the synergy between legal science and computer science will be examined, highlighting their impact on the administration of justice. Finally, methodological guidelines for addressing this interdisciplinarity will be outlined, aiming for proper structuring and legal framing.